Consumer Debt and Default: A Macro Perspective - Florian Exler; Michèle Tertilt (Institute of Labor Economics (IZA), 2020)
In this survey, we review the quantitative macroeconomic literature analyzing consumer debt and default. We start by providing an overview of consumer bankruptcy law in the US and document the relevant institutional changes over time. We proceed with a comprehensive empirical section, describing key facts about consumer debt, defaults and delinquencies, as well as charge-off and interest rates for the United States. In addition to the evolution of these variables over time, we construct life-cycle profiles using data from the Survey of Consumer Finances and show that debt and defaults display a clear hump-shaped profile by age. Third, we show how credit card debt has evolved along the income distribution. Finally, we document a large amount of heterogeneity in credit card interest rates across consumers. In the second part of the survey, we describe what has by now become the workhorse model of consumer credit and default. We discuss a quantitative version of the model and use it to decompose the main reasons for default. We also use the model to illustrate how the details of default costs matter. The remainder of the survey then discusses the literature centered around two questions. First, what are the welfare implications of various bankruptcy laws? And second, what caused the rise in filings over time? We end with a discussion of open questions and fruitful avenues for future research
Keywords: C60; E20; G20; O30; 330; consumer debt; bankruptcy; chapter 7; default; credit cards; charge-offs